The role of gut microbiome in inflammatory skin disorders: a systematic review - Suci Widhiati; Dewajani Purnomosari; Tri Wibawa; Hardyanto Soebono (PAGEPress Publications, 2021)
The close relationship between the intestine and the skin has been widely stated, seen from gastrointestinal (GI) disorders often accompanied by skin manifestations. Exactly how the gut microbiome is related to skin inflammation and influences the pathophysiology mechanism of skin disorders are still unclear. Many studies have shown a two-way relationship between gut and skin associated with GI health and skin homeostasis and allostasis. This systematic review aimed to explore the associations between the gut microbiome with inflammatory skin disorders, such as acne, psoriasis, atopic dermatitis, and urticaria, and to discover the advanced concept of this relationship. Methods: The literature search was limited to any articles published up to December 2020 using PubMed and EBSCOHost. The review followed the PRISMA guidelines for conducting a systematic review. Result: Of the 319 articles screened based on title and abstract, 111 articles underwent full-text screening. Of these, 23 articles met our inclusion criteria, comprising 13 AD, three psoriasis, four acne vulgaris, and four chronic urticaria articles. Discussion: Acne vulgaris, atopic dermatitis, psoriasis, and chronic urticaria are inflammation skin disorders that were studied recently to ascertain the relationship of these disorders with dysbiosis of the GI microbiome. All acne vulgaris, psoriasis, and chronic urticaria studies stated the association of gut microbiome with skin manifestations. However, the results in atopic dermatitis are still conflicting. Most of the articles agree that Bifidobacterium plays an essential role as anti-inflammation bacteria, and Proteobacteria and Enterobacteria impact inflammation in inflammatory skin disorder.